PASTOR PAROKI DAN PELAYANAN MASALAH PERKAWINAN - Ngutra, Seno (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2019)
“There are many problems that happen in the ministry of the Pastor as Parish Priest. The Parist priest is called to give solution for the people who are facing their daily problems. One of the problem in the ministry is marriage cases. This article is dedicated to the Parish Priest as guideline in his ministry, especially in the working on marriage cases. The spirit behind the rules in the Church is for the sake of souls.